Superconductivity in Bi-Pb-Sr-Ca-Cu-O ceramics with YBCO as additive - Arlina, A.; Halim, S.A.; Kechik, M.M.A.; Chen, S.K. (Elsevier, 2015)
The effect of YBCO addition on the superconductivity in Bi1.6Pb0.4Sr2Ca2Cu3Oδ (BSCCO) systems was studied. The samples were prepared through solid state reaction and the properties have been investigated via resistivity measurement (R–T), Scanning electron microscope (SEM) and X-ray diffraction (XRD) analysis. The highest resistivity measurement was observed for the samples with x = 0.02 of YBCO at 102 K. Generally, all samples exhibit metallic behavior above transition temperature TC onset. From the XRD data, it is observed that the volume percentage of the Bi-2223 phase is initially 75% for the pure samples but decreases till 25% with the increasing Bi-2212 phase. Analysis of the temperature dependence of the AC susceptibility near the transition temperature has been done. The field effect on AC susceptibility was measured. The field increased from 0.05 Oe to 2.00 Oe and the peak temperature (TP) gradually decreased to lower temperature from 107.0 K to 108.5 K.